Systematic variation of cyanobuta-1,3-dienes and expanded tetracyanoquinodimethane analogues as electron acceptors in photoactive, rigid porphyrin conjugates - Urner, Lorenz M.; Sekita, Michael; Trapp, Nils; Schweizer, W. Bernd; Woerle, Michael; Gisselbrecht, Jean-Paul; Boudon, Corinne; Guldi, Dirk Michael; Diederich, Francois (European Journal of Organic Chemistry, 2015)
We report on a homologous series of nine electron donor-acceptor systems featuring push-pull chromophores as electron acceptors, which are accessible by a cycloaddition-retroelectrocyclization (CA-RE) reaction. The conjugates comprise a ZnII porphyrin as electron donor, which is connected through either a rigid phenylene-ethynylene-phenylene (PEP)-bicyclo[2.2.2]octane or a PEP-trans-decahydroquinoline spacer to different anilino-substituted multicyanobutadienes or extended tetracyanoquinodimethane analogues with first reduction potentials ranging from-1.78 to-0.58 V vs. Fc+/Fc. Characterization of the conjugates includes X-ray crystallography, electrochemistry, DFT calculations, and fluorescence spectroscopy. The extent of ZnII porphyrin fluorescence quenching correlates with the strength of the electron acceptor. Overall, we demonstrate the synthetic feasibility of rationally modulating the acceptor strength by means of the CA-RE reaction in geometrically well-defined electron donor-acceptor conjugates.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Donor-acceptor systems; Electron transfer; Energy conversion; Photochemistry; Porphyrinoids